Pengaruh Manajemen Modal Kerja Terhadap Profitabilitas Pada Perusahaan Sub Sektor Makanan dan Minuman Yang Terdaftar Di Bursa Efek Indonesia (BEI) - Leni Hartati; Apollo Apollo; Endri Endri; Agustina Kurniasih (Jurnal Doktor Manajemen (JDM), 2022)
The existence of working capital management is very important for a company to support all activities of a company. This is because the management of working capital required by the company will determine business continuity. This study aims to examine and analyze the effect of cash turnover, accounts receivable turnover and inventory turnover on return on assets (ROA) in food and beverage subsector companies listed on the Indonesia Stock Exchange (IDX). The hypothesis tested is the independent variable, namely cash turnover, accounts receivable turnover and inventory turnover, the dependent variable is return on assets (ROA). The sample used is secondary data from financial statements listed on the Indonesia Stock Exchange (IDX). Sampling was done through purposive sampling and samples that met the selection criteria. The sample used is 21 companies. Observations were made for 5 years starting from 2016 - 2020. Data Testing and Data Processing Techniques in this study used quantitative analysis. Furthermore, it will be analyzed and tested hypotheses with the help of computer programs, namely Microsoft Excel and Eviews 10. The results showed that simultaneously cash turnover, accounts receivable turnover and inventory turnover, jointly had a significant effect on the dependent variable ROA, and partially cash turnover and inventory turnover. Inventory turnover has no significant effect on the dependent variable return on assets (ROA) while receivables turnover has a significant effect on the dependent variable return on assets (ROA).